1999
DOI: 10.1055/s-0037-1614600
|View full text |Cite
|
Sign up to set email alerts
|

Increased C-reactive Protein Levels during Short-term Hormone Replacement Therapy in Healthy Postmenopausal Women

Abstract: Summary Objective: To study the short-term effect of unopposed oestradiol (E2) and sequentially combined hormone replacement therapy (E2 + P) on C-reactive protein (CRP) in healthy postmenopausal women. Design: Prospective, randomised, placebo-controlled 12-week study. Sixty healthy, normotensive, non-hysterectomised postmenopausal women received either placebo (N = 16) or daily 2 mg micronised oestradiol, either unopposed (N = 16, E2 group) or sequentially combined with a progestagen on 14 days of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
61
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 14 publications
12
61
1
1
Order By: Relevance
“…However, this is unlikely because previous studies indicated that oral estrogen has been shown to consistently increase acute phase protein CRP regardless of specific preparations (ie, oral-conjugated estrogens or oral 17␤-estradiol, or estradiol valerate). 11,12 Our observation may have important clinical implication for several reasons. First, elevated SAA levels are independently associated with adverse cardiovascular events in women, 1 possibly by their direct proinflammatory and proatherogenic effects.…”
Section: Discussionmentioning
confidence: 83%
“…However, this is unlikely because previous studies indicated that oral estrogen has been shown to consistently increase acute phase protein CRP regardless of specific preparations (ie, oral-conjugated estrogens or oral 17␤-estradiol, or estradiol valerate). 11,12 Our observation may have important clinical implication for several reasons. First, elevated SAA levels are independently associated with adverse cardiovascular events in women, 1 possibly by their direct proinflammatory and proatherogenic effects.…”
Section: Discussionmentioning
confidence: 83%
“…43 Furthermore, lowering fibrinogen levels via drugs may not have the same effect as naturally low levels. van Baal et al 44 observed an estrogen-associated 12% reduction in clottable fibrinogen but no change in fibrinogen antigen, suggesting that estrogen may act on fibrinogen clotting, not synthesis.…”
Section: Effects Of Serms On Hemostasismentioning
confidence: 99%
“…The PEPI study 1 was a 3-year randomized trial, whereas Ridker et al presented cross-sectional results from the Women's Health Study (WHS). 2 In addition, the women in our study were all diabetics, and CRP levels are known to be significantly raised in diabetics. Our sample size was smaller than the American studies.…”
mentioning
confidence: 90%